Experimental determination of the bulk Rashba parameters in BiTeBr. (20th January 2017) - Martin, C.; Suslov, A. V.; Buvaev, S.; Hebard, A. F.; Bugnon, P.; Berger, H.; Magrez, A.; Tanner, D. B.
Abstract: Shubnikov-de Haas (SdH) oscillations, Hall effect, and optical reflectance measurements have been performed on single crystals of BiTeBr. Under magnetic fields up to 32 tesla and at temperatures as low as 0.4 K, the SdH data shows a single oscillation frequency . The combined transport and optical studies establish that the SdH effect originates from the Rashba spin-split bulk conduction band, with the chemical potential situated about 13 meV below the crossing (Dirac) point. The bulk carrier concentration was and the effective mass . Combining SdH and optical data, we reliably determine the Rashba parameters for the bulk conduction band of BiTeBr: the Rashba energy and the momentum spin-split . Hence, the bulk Rashba coupling strength is found to be 1.7 eVÅ.